2018
DOI: 10.1038/s41591-018-0160-1
|View full text |Cite
|
Sign up to set email alerts
|

Depicting the composition of gut microbiota in a population with varied ethnic origins but shared geography

Abstract: Trillions of microorganisms inhabit the human gut and are regarded as potential key factors for health. Characteristics such as diet, lifestyle, or genetics can shape the composition of the gut microbiota and are usually shared by individuals from comparable ethnic origin. So far, most studies assessing how ethnicity relates to the intestinal microbiota compared small groups living at separate geographical locations. Using fecal 16S ribosomal RNA gene sequencing in 2,084 participants of the Healthy Life in an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
408
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 490 publications
(426 citation statements)
references
References 50 publications
13
408
2
3
Order By: Relevance
“…These data confirm recent findings that demonstrate the predominance of host location and ethnicity, with respect to diet, as determinants of human GM variation [14,15]. However, despite the overall Western-like configuration, the MPD-associated GM structure stands out from that of Italians adhering to the MD for a much higher degree of biodiversity, which well approximates that observed in traditional hunter-gatherers.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…These data confirm recent findings that demonstrate the predominance of host location and ethnicity, with respect to diet, as determinants of human GM variation [14,15]. However, despite the overall Western-like configuration, the MPD-associated GM structure stands out from that of Italians adhering to the MD for a much higher degree of biodiversity, which well approximates that observed in traditional hunter-gatherers.…”
Section: Discussionsupporting
confidence: 89%
“…These data confirm recent findings that demonstrate the predominance of host location and ethnicity, with respect to diet, as determinants of human GM variation. 14, 15 However, despite the overall Western-like configuration, the MPD-associated GM structure stands out from that of Italians adhering to the MD for a much higher degree of biodiversity, which well approximates that observed in traditional hunter-gatherers. Since the Italian subjects of our cohort share the provenance and all that it entails, including the lifestyle, it can be hypothesized that the MPD-associated bloom in GM diversity is accounted for by the peculiarities of the MPD compared to the MD.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The gut microbiome has been implicated in a growing list of complex diseases, showing great potential for the diagnosis and treatment of metabolic, autoimmune and neurological diseases as well as cancer. While case-control studies have been illuminating 1 , recently published studies have emphasized difficulty in extrapolating to natural cohorts due to heterogeneity in location and ethnicity 23 . So far only a few cohorts made use of metagenomic shotgun sequencing instead of 16S rRNA gene amplicon sequencing, the largest being the LifeLines Deep cohort (n=1,135, 32 million reads per sample) from the Netherlands 47 Fecal or plasma metabolites are more or less included in gut microbiome studies, but the conclusions usually did not go beyond short-chain fatty acids (SCFA), amino acids, vitamin B complex or bile acids.…”
mentioning
confidence: 99%
“…These vast differences in the diet are likely to influence the 72 microbial composition and thus protect or predispose to the development of CRC. In fact, is has 73 been shown that the gut microbiome is significantly different in individuals of different ethnicity, 74 living in the same geographical area [15]. Since dietary factors are likely to directly contribute to 75 the microbial composition and thus to the risk of developing CRC, change in the dietary patterns 76 can be an important strategy in the prevention and treatment of CRC [16].…”
mentioning
confidence: 99%